Assessing Mergers and Acquisitions on Acquiring Firms' Profitability: A Comparative Analysis of Pre- and Post-Transaction Performance in ASEAN Stock Market - Theja, Dea Devina; Ratnadi, Ni Made Dwi; Budiartha, I Ketut; Gayatri, Gayatri; Ariyanto, Dodik; Sukartha, P. D'yan Yaniartha (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 19 No 2 (2024), 2024)
The intense competition in today’s global market drives companies to adopt strategies like mergers and acquisitions (M&A) to enhance their competitive edge. This study, focusing on public companies in ASEAN, examines the relationship between M&A activity and acquiring firms' performance through three profitability ratios while accounting for the type of M&A. Using purposive sampling, 188 paired samples were analyzed through a paired sample t-test to assess profitability changes before and after M&A transactions. An independent sample t-test was conducted on 254 samples to compare the profitability of related versus unrelated M&As. The findings reveal that M&A activities are generally associated with a decline in profitability, particularly in return on assets (ROA) and return on equity (ROE). No significant difference in profitability was found between related and unrelated M&As. The results align with agency and hubris theories, contributing to the ongoing discourse on the implications of M&As on acquiring firms' performance. Keywords : business combination, M&A, profitability